Abnormal von Willebrand factor secretion, factor VIII stabilization and thrombus dynamics in type 2N von Willebrand disease mice. (17th July 2017) - Swystun, L. L.; Georgescu, I.; Mewburn, J.; Deforest, M.; Nesbitt, K.; Hebert, K.; Dwyer, C.; Brown, C.; Notley, C.; Lillicrap, D.
Abstract : Essentials Type 2N von Willebrand disease involves impaired von Willebrand factor to factor VIII binding. Type 2N von Willebrand disease mutations exhibit qualitative and mild quantitative deficiencies. Type 2N von Willebrand disease mice exhibit unstable venous hemostatic thrombi. The factor VIII‐binding ability of von Willebrand factor regulates arteriole thrombosis dynamics. Summary: Background: von Willebrand factor (VWF) and factor VIII (FVIII) circulate as a non‐covalent complex, with VWF serving as the carrier for FVIII. VWF indirectly influences secondary hemostasis by stabilizing FVIII and transporting it to the site of primary hemostasis. Type 2N von Willebrand disease involves impaired binding of VWF to FVIII, resulting in decreased plasma levels of FVIII. Objectives: In these studies, we characterize the impact of three type 2N VWD variants (R763A, R854Q, R816W) on VWF secretion, FVIII stabilization and thrombus formation in a murine model. Methods: Type 2N VWD mice were generated by hydrodynamic injections of mutant murine VWF cDNAs and the influence of these variants on VWF secretion and FVIII binding was evaluated. In vivo hemostasis and the dynamics of thrombus formation and embolization were assessed using a murine tail vein transection hemostasis model and an intravital thrombosis model in the cremaster arterioles. Results: Type 2N VWD variants were associated with decreased VWF secretion using cell and animal‐based models. FVIII‐binding to type 2N variants was impaired in vitro and was variably stabilized in vivo by expressed or infused 2N variant VWF protein. Both transgenic type 2N VWD and FVIII knockout (KO) mice demonstrated impaired thrombus formation associated with decreased thrombus stability. Conclusions: The type 2N VWD phenotype can be recapitulated in a murine model and is associated with both quantitative and qualitative VWF deficiencies and impaired thrombus formation. Patients with type 2N VWD may have normal primary hemostasis formation but decreased thrombus stability related to ineffective secondary hemostasis.